2014
DOI: 10.4999/uhod.12008
|View full text |Cite
|
Sign up to set email alerts
|

Complementary/Alternative Medicine Experience in Cancer Patients: A Questionnaire-Based Survey.

Abstract: A study was designed to evaluate the frequency of complementary/alternative therapy (CAM) knowledge and usage in cancer patients. A 23-item survey questionnaire was administered to 494 patients who received chemotherapy in the medical oncology department of three hospitals between June 2011 and December 2011. After giving written informed consent, patients completed a selfadministered questionnaire. Differences among participants were assessed by using the SPSS 17.0 software. Of the 494 patients, 48% had heard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
1
7
1
4
Order By: Relevance
“…The results from this study also showed that patients with 3 or more comorbidities were twice as likely to use CAM compared with those who did not have comorbidities. This supports a previous study 41 that found that cancer patients with comorbidities are more likely to use CAM. This finding suggested that people who experienced many health problems were more likely to use alternative medicine for their general health because they may believe that CAM provides additional protection from the effects of treatments, the disease, or comorbidities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results from this study also showed that patients with 3 or more comorbidities were twice as likely to use CAM compared with those who did not have comorbidities. This supports a previous study 41 that found that cancer patients with comorbidities are more likely to use CAM. This finding suggested that people who experienced many health problems were more likely to use alternative medicine for their general health because they may believe that CAM provides additional protection from the effects of treatments, the disease, or comorbidities.…”
Section: Discussionsupporting
confidence: 92%
“…Many cancer centers in the developed world have incorporated complementary practices such as integrative therapies within conventional treatment centers. 41 Innovative approaches to bring in patient values in discussions into mainstream practice are much needed in Asian countries where paternalistic medicine is still widely practiced. Second, the study sample was drawn from an urban population that contains a large number of Chinese, which may inadvertently have led to a higher proportion of TCM users among the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Gender is an essential determinant in making decisions about the use of CAM. In contrast to our own studies, those conducted by Hierl et al [12], Wode et al [28], Demir et al [25], Dogu et al [34], Garland et al [31] and Stanisz et al [16] prove that women decide to use CAM more often than men.…”
Section: Mecontrasting
confidence: 91%
“…Bir diğer çalışmada ise ısırgan otu kullanımı 89.6% bulunmuştur (5). Doğu ve arkadaşlarının çalışmasında da kullanılan TAT'ların genellikle bitkisel ürünler olduğu ve en sık kullanılan bitkisel ürünün ise ısırgan otu olduğu belirtilmiştir (7). Taş ve arkadaşlarının çalışmasında ise ısırgan otu kullanımı 88% olarak belirtilmiş olup; kullanıcıların 56%'sı bu ürünü tek başına kullanırken, 32%'si ise diğer bitkisel ürünlerle karıştırmaktadır (31).…”
Section: Gereç Ve Yöntemunclassified
“…Çalışmamızda da hastaların bu tedavileri neden kullandıkları sorusuna verilen en sık cevap bu ürünlerin hastalığın iyileşme sürecinde fayda göstereceğine inanmalarıydı (n:17, 80.9%). Çalışmamız ile uyumlu olarak hem ülkemizde hemde yurtdışı çalışmalarda TAT kullanma nedenleri arasında ensık neden; hastalığın iyileşme süresine katkı sağlamak ve hastalığa iyi gelmesine inanmak olarak belirtilmektedir (5,6,7,23,32…”
Section: Gereç Ve Yöntemunclassified